2000
DOI: 10.1046/j.1365-2125.2000.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state pharmacokinetics of (R)‐ and (S)‐methadone in methadone maintenance patients

Abstract: Aims To investigate the steady-state pharmacokinetics of (R)-and (S)-methadone in a methadone maintenance population. Methods Eighteen patients recruited from a public methadone maintenance program underwent an interdosing interval pharmacokinetic study. Plasma and urine samples were collected and analysed for methadone and its major metabolite (EDDP) using stereoselective h.p.l.c. Methadone plasma protein binding was examined using ultra®ltration, and plasma a 1 -acid glycoprotein concentrations were quanti®e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 46 publications
9
128
3
1
Order By: Relevance
“…The area under the plasma concentration-time curve (AUC) during the dosing interval () (AUC from 0 to 24 h [AUC 0-24 ] for methadone and AUC 0-12 for voriconazole and the N-oxide metabolite) was estimated using linear/log-trapezoidal approximation. The approximate linearity of methadone steady-state pharmacokinetics at daily doses ranging from 7.5 mg to 130 mg was demonstrated previously (13). For the purpose of presenting mean pharmacokinetic profiles and mean parameter values at a given dose, the methadone concentrations were dose normalized to a 100-mg equivalent dose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the plasma concentration-time curve (AUC) during the dosing interval () (AUC from 0 to 24 h [AUC 0-24 ] for methadone and AUC 0-12 for voriconazole and the N-oxide metabolite) was estimated using linear/log-trapezoidal approximation. The approximate linearity of methadone steady-state pharmacokinetics at daily doses ranging from 7.5 mg to 130 mg was demonstrated previously (13). For the purpose of presenting mean pharmacokinetic profiles and mean parameter values at a given dose, the methadone concentrations were dose normalized to a 100-mg equivalent dose.…”
Section: Methodsmentioning
confidence: 99%
“…These calculations were based on the intersubject coefficient of variation (55%) of the steady-state AUC 0-24 for (R)-methadone (13).…”
Section: Statistical Analysis (I) Sample Size Determinationmentioning
confidence: 99%
“…Sa pharmacocinétique présente une forte variabilité interindividuelle, d'une part du fait qu'elle est le substrat de la glycoprotéine P (P-gP) [8], et d'autre part parce qu'elle subit un métabolisme par le cytochrome 3A4, à l'origine d'une N-déméthylation suivie d'une cyclisation pour aboutir au mé-tabolite majeur de la méthadone, l'EDDP. C'est essentiellement la forme (S) qui subit le métabolisme, la forme (R) étant principalement éliminée sous forme inchangée [9]. Cette éli-mination se fait pour un tiers dans les urines sous forme inchangée, un tiers dans les urines sous forme d'EDDP et un tiers dans les fécès sous forme d'EDDP.…”
Section: Pharmacocinétiqueunclassified
“…It is a vital public health strategy for HIV/AIDS risk reduction [1]. Variability in methadone clearance, susceptibility to drug interactions, and a long elimination half-life can however be major impediments to optimal methadone use [2,3]. In in vitro drug metabolism studies, CYP3A4 has been implicated in methadone metabolism [4].…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro drug metabolism studies, CYP3A4 has been implicated in methadone metabolism [4]. Authors have suggested dosing guidelines for methadone and warned about the potential for CYP3A4-mediated interactions and suggested the need to adjust doses accordingly [2,3,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%